Low-dimensional ScO2 with tunable electronic and magnetic properties: first-principles studies. (16th November 2015) - Zhang, Hui; Tong, Chuan-Jia; Wu, Jian; Yin, Wen-Jin; Zhang, Yan-Ning
Abstract: Transition metal dichalcogenides (TMDs) have attracted extensive attention due to their appealing properties for device applications. In this work, we explored the structure stability, electronic structure and magnetism of low-dimensional scandium dioxides, ScO2, by using the first-principles calculations. The results demonstrate that bulk ScO2, monolayers and nanoribbons (NRs) are thermodynamically stable, implying a high possibility of fabricating ScO2 nanocrystals in experiments. Despite the metallic characteristics of bulk ScO2, low-dimensional ScO2 possesses various electronic behaviors that can be further modulated by crystal structure and dimensionality. The results also show that the ground states of ScO2 monolayers and NRs are ferromagnetic (FM) with about 1 μ B per ScO2 formula. Our studies expand a new realm in low-dimensional TMDs, with tunable electronic and magnetic properties.